Spectroscopic ellipsometry and X-ray photoelectron comparative studies of tribofilms formed on cast iron surfaces. (September 2017) - Miranda-Medina, M.L.; Spiller, S.; Vernes, A.; Jech, M.
Abstract: In this paper, tribofilms generated in a model piston ring – cylinder liner setup within a tribometer environment were investigated by surface and optical techniques. The cylinder liner material was grey cast iron of an automotive grade, while the piston ring material was nitrided steel and the lubricant consisted of fully formulated oil with zinc dialkyldithiophosphate additives. X-ray photoelectron spectroscopy was used to determine the chemical composition of the resulting tribofilms, and as comparative technique for the evaluation of their thicknesses. Ellipsometrical measurements were modelled by using an effective medium approximation by including depolarisation effects to describe the optical properties, thickness and uniformity of the films. The adjustment of the effective medium model on basis of the X-ray photoelectron spectroscopy findings resulted in a good agreement between the estimations for tribofilm thicknesses in both experimental methods. Highlights: Surface evolution during boundary lubricating sliding in a piston ring-cylinder liner configuration. Chemical compostion of ZDDP reaction films obtained by XPS and tribofilm thickness estimated by spectroscopy ellipsometry. Correlation between piston ring wear and tribofilm formed on a cylinder liner.